Developing a Bilingual Creative Tourism Map According to the New Normal of the Chi River Basin Community, Baan Don Bom, Khon Kaen Province - Janthadee, Somsak (Al-HIKMAH Journal, 2024)
The objectives of this research article were: 1) to study the community context, history, background, cultural traditions, economic and social conditions of the Chi River basin community, Baan Don Bom, Khon Kaen Province 2) to develop a bilingual creative tourism map in line with the new normal of the Chi River basin community, Baan Don Bom, Khon Kaen Province 3) to disseminate tourist information through general map formats and map websites both in Thai and English to promote community tourism in the new normal era using methods of studying related research documents, field data collection, interviews, and observation. The results found that 1) the potential for creative tourism management of the Chi River basin community, Baan Don Bom, Khon Kaen Province, was at a high level. There are a variety of tourist attractions including natural resources and beautiful ecotourism attractions. There are ready infrastructure for public utilities, participation of all sectors, leaders have high leadership qualities, and people are ready to manage tourism 2) the development of creative tourism maps in bilingual format received great support from both community leaders and local people. All sectors are involved in expressing opinions, presenting guidelines for developing tourism maps, and participating in learning about creative tourist maps in the form of general maps and tourist map websites (digital maps) in both Thai and English, and 3) dissemination of tourist information through general map formats and tourist map websites both in Thai and English to promote community tourism in the new normal era. It was found that there was great interest from the people of Don Bom Village including foreign citizens and tourists. This is reflected in the number of visitors to the website currently at 1,950 times.